Linguistics issues in multicultural contexts - Mat Awal, Norsimah (Universiti Putra Malaysia Press, 2011)
There are diverse issues on language in a multi-racial society which provides a rich ground of inquiry into the linguistic analysis of those issues. Investigations of these linguistic issues will help us to understand better the varied and rich cultures which permeate in a multi-racial society. As a result, this would lead to a better intercultural communication in the global community. The linguistic issues discussed in this book focus on syntax, semantics, stylistics, language varieties and translation. The presentation of core issues in linguistics and language in applied linguistics, would certainly appeal to a wide section of academics and language users. Most studies in this book are based on local Malaysian multiracial setting, except for one, which investigates the effect of accent in inter-personal communication among non-native speakers of English in the United States.